2021
DOI: 10.1029/2020ms002239
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Exascale Earth System Model Simulations With High Vertical Resolution in the Lower Troposphere

Abstract: High vertical resolution in the lower troposphere is a crucial ingredient to improve marine stratocumulus (Sc) in GCMs.• These simulations are expensive and require time step adjustment, which intro-10 duces sensitivities. 11• Vertical resolution alone cannot improve coastal Sc, likely concurrent increases in 12 horizontal resolution are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…Among the four simulations, the potential temperature profiles in the high vertical resolution simulations (ne30_ FIVE and ne120_FIVE) have higher PBL inversion top and stronger inversion strength over the offshore region of Peru (Figure 3a), resulting in a higher cloud top and thicker cloud deck compared to their low vertical resolution simulation counterparts. The sharper temperature inversion represented by the high vertical resolution simulations agrees with Bogenschutz et al (2021) who found that high vertical resolution is needed to resolve the cloud top cooling that occurs over a thin layer in the marine stratocumulus regime, which is a crucial ingredient for the maintenance of these clouds. Although this process is better represented in the high vertical resolution simulations, we note a systematic bias for the cloud top to be too high for these experiments when compared to the C3M observations.…”
Section: Cloud and Turbulence Vertical Structuresupporting
confidence: 85%
See 1 more Smart Citation
“…Among the four simulations, the potential temperature profiles in the high vertical resolution simulations (ne30_ FIVE and ne120_FIVE) have higher PBL inversion top and stronger inversion strength over the offshore region of Peru (Figure 3a), resulting in a higher cloud top and thicker cloud deck compared to their low vertical resolution simulation counterparts. The sharper temperature inversion represented by the high vertical resolution simulations agrees with Bogenschutz et al (2021) who found that high vertical resolution is needed to resolve the cloud top cooling that occurs over a thin layer in the marine stratocumulus regime, which is a crucial ingredient for the maintenance of these clouds. Although this process is better represented in the high vertical resolution simulations, we note a systematic bias for the cloud top to be too high for these experiments when compared to the C3M observations.…”
Section: Cloud and Turbulence Vertical Structuresupporting
confidence: 85%
“…Bogenschutz et al (2012) show that single column model simulations with the Cloud Layers Unified By-Binormals (CLUBB) (Larson & Golaz, 2005) parameterization performs best in the stratocumulus and transitional regimes when high vertical resolution is used in the lower troposphere. More recently, Bogenschutz et al (2021) show that coarse vertical resolution in the Energy Exascale Earth System Model (E3SM) (Golaz et al, 2019) is a significant cause of low-level cloud bias because CLUBB cannot realize the sharp temperature and moisture gradients often found at the top of subtropical stratocumulus layers. Bogenschutz et al ( 2021) demonstrated that increasing vertical resolution in E3SM, toward those…”
mentioning
confidence: 99%
“…For vertical resolution dependency at a given horizontal resolution (Figures 9c and 9d), cloud occurrence tends to increase at high vertical BL-resolution both in the Tropics and the Subtropical regions; the liquid cloudy column fraction tends to be high at high vertical BL-resolution both in the Tropics region and in the Subtropics region, except for DY16-L128. In a conventional GCM, a similar trend of vertical resolution dependency for shallow convection has been reported both in the Tropics and the Subtropics (Bogenschutz et al, 2021;Lee et al, 2021). Xu and Cheng (2013) also found that the global mean low-cloud amount simulated by a GCM using super parameterization (i.e., a multiscale modeling framework; DeMott et al, 2010) increases at high vertical resolution and approaches the satellite-observed low-cloud amount.…”
Section: Sensitivities For Cloud Characteristicssupporting
confidence: 57%
“…No reduction of E3SM time step is required with any of the E3SM-FIVE configurations, compared to the E3SM benchmark runs, which is partially why E3SM-FIVE greatly reduces computational cost compared with high vertical resolution simulations without FIVE. The time step constraint in the benchmark simulations is likely associated with the ZM deep convection scheme, which has been tested in a benchmark sensitivity simulation (see Bogenschutz et al, 2021). In addition, the ZM deep convection scheme appears to be sensitive to higher vertical resolution, and it results in degrading skill scores of precipitation and clouds in the deep convective tropics as the vertical resolution becomes very fine.…”
Section: Discussionmentioning
confidence: 99%